Toward assessing the interlanguage of the Filipino learner an error analysis of the oral composition of Grades V and VI pupils - Romero, Perlita P. 1944- (1980)
This dissertation made an attempt to describe the Interlanguage of Grades V and VI pupils by means of error analysis. Findings showed that basic similarities appeared in the speech of children learning English as a first and as a second language. Similar to the first language learners, Filipino learners or L2 learners keep grammatical frills to a minimum. They disregard exceptions to rules and they use the regular forms of syntactic and morphological constructions. Thus, errors which Filipino learners of English make are developmental and systematic and are reflective of the nature of their interlanguage.
Thesis (Ph.D.)--University of the Philippines, Diliman.
Typescript.
Vita.
Keywords: Interlanguage (language learning).; English language -- Errors of usage. -- Philippines